Development and Characterization of Novel Floating-Mucoadhesive Tablets Bearing Venlafaxine Hydrochloride - Raghvendra Misra; Peeyush Bhardwaj (Scientifica)
The present investigation is concerned about the development of floating bioadhesive drug delivery system of venlafaxine hydrochloride which after oral administration exhibits a unique combination of floating and bioadhesion to prolong gastric residence time and increase drug bioavailability within the stomach. The floating bioadhesive tablets were prepared by the wet granulation method using different ratios of hydroxypropyl methyl cellulose (HPMC K4MCR) and Carbopol 934PNF as polymers. Sodium bicarbonate (NaHCO3) and citric acid were used as gas (CO2) generating agents. Tablets were characterized for floating properties, in vitro drug release, detachment force, and swelling index. The concentration of hydroxypropyl methyl cellulose and Carbopol 934PNF significantly affects the in vitro drug release, floating properties, detachment force, and swelling properties of the tablets. The optimized formulation showed the floating lag time 72±2.49 seconds and duration of floating 24.50±0.74 hr. The in vitro release studies and floating behavior were studied in simulated gastric fluid (SGF) at pH 1.2. Different drug release kinetics models were also applied. The in vitro drug release from tablets was sufficiently sustained (more than 18 hr) and the Fickian transports of the drug from the tablets were confirmed. The radiological evidence suggests that the tablets remained buoyant and altered position in the stomach of albino rabbit and mean gastric residence time was prolonged (more than > 6 hr).